Intermolecular Interaction of [60]Fullerene with Tröger's Base Analogues - Yamada, Michio; Tokutomi, Konomi; Takehara, Ayaka; Sakai, Yusuke; Maeda, Yutaka; Hasegawa, Tadashi (Fullerenes, nanotubes, and carbon nanostructures, 2014)
Tröger's base (TB, 1) and its analogues were synthesized and were subject to the titration experiments to evaluate their ability of supramolecular complexation with C 60 . Results demonstrate clearly that the fluorene-based TB analogue (2) and the bioctylfluorene-based TB analogue (3) show 1:1 binding with C 60 to form the corresponding complexes while TB 1 does not. Titration experiments exhibited that the association constant (K ass ) of 3/C 60 (48.1 ± 7.9 M −1 ) was larger than that of 2/C 60 (13.7 ± 1.4 M −1 ) . The formation of the 1:1 binding complexes 2/C 60 and 3/C 60 was also confirmed by MALDI-TOF mass spectrometry. Theoretical calculations suggest that 2 and 3 have appropriate cavities to embrace C 60 . These findings indicate that not only the π/π interaction between the fluorene moieties and the C 60 surface but also the CH/π interaction between the octyl groups and the C 60 surface serve efficiently in the supramolecular complexation with C 60 .